Incorporation of olive pomace ingredients in yoghurt as source of fibre and hydroxytyrosol: bioactivity and stability of throughout gastrointestinal digestion - Ribeiro, Tânia Bragança (2019)
Tânia I. B. Ribeiro thanks the Fundação para a Ciência e Tecnologia (FCT), Portugal for the PhD Grant SFRH/BDE/108271/2015, the financial support of BLC3 Association – Technology and Innovation Campus and the mentoring of Frulact and Comendador Arménio Miranda.